FULL-FLEDGED INFLATION TARGETING FRAMEWORK DAN PERSISTENSI INFLASI - Rachman Hakim (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
Setting the inflation rate may look simple but certainly not easy. This can be evidenced by frequent melencengnya inflation target has been set by Bank Indonesia. To overcome this, the 2004 Law No. 3 Article 7 were excluded, thus changing the policy framework of inflation targeting lite be a full-fledged inflation targeting. This means that Bank Indonesia will focus on regulating the rate of inflation only. The purpose of this study to determine whether the rate of inflation to be more easily controlled in the period of full-fledged inflation targeting. The method used is the autoregressive model estimation. The results showed that the application of full-fledged inflation targeting has not had a positive impact in regulating the rate of inflation. In the period 2005-2015, was inflation is still very difficult to control or tend to be persistent. Interestingly, this was due to the strong influence of the global economy on the Indonesian econom